ELECTRICITY AND ECONOMIC GROWTH IN INDONESIA’S PROVINCE OF ACEH - Fahrul Rizal (Aceh International Journal of Social Science, 2014)
Abstract: This paper is distinguished from previous research in term of using sectoral electricity consumption data (residential, commercial, public, and industrial) rather than of using aggregate electricity consumption data in order to examine the relationship between electricity and economic growth. The vector error correction model is employed to scrutinize the linkage based on data covering time span 1995-2031 in Indonesia’s Province of Aceh. The empirical evidences indicate that the long-run bidirectional relationship exists between, (1) commercial electricity consumption and economic growth and, (2) public electricity consumption and economic growth. In addition, the short-run bidirectional relationship exists between economic growth and all of the sectoral electricity consumption. The results imply that the government policy for power development is purposed to maintain the bidirectional causality between economic growth and electricity consumption. Keywords: Sectoral Electricity Consumption, Economic Growth, Aceh, Vector Error Correction Model.